LEGAL AND INSTITUTIONAL CHALLENGES IN THE MANAGEMENT OF TRANSBOUNDARY RIVERS (THE AMUDARYA AND THE SYRDARYA) (Eureka Journal of Humanities and Social Research, 2026)
The article examines the key legal and institutional challenges in the management of transboundary rivers, using the Amudarya and Syrdarya basins as case studies. These rivers play a crucial role in the socio-economic development and environmental sustainability of Central Asia, yet their governance remains complex and contested. The study analyzes deficiencies in international legal frameworks, institutional fragmentation, and coordination mechanisms among riparian states. Special attention is given to the gap between formal legal norms and actual water management practices. The findings highlight the need for strengthened basin-level institutions, improved legal harmonization, and adaptive governance approaches in the context of climate change and increasing water scarcity.
Keywords: Transboundary rivers; Amudarya; Syrdarya; international water law; institutional governance; Central Asia; water security; legal frameworks; regional cooperation; climate change.